2016
DOI: 10.3390/su8010066
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation into Real Estate Investment and Economic Growth in China: A Dynamic Panel Data Approach

Abstract: Using a dynamic panel data approach to analyze national-level and province-level data in China from 2000 to 2012, this paper studies how real estate investment affects Chinese economic growth. We find that real estate investment has significantly positive contemporaneous effects on economic growth on both national and regional levels. Surprisingly, we also find that real estate investment has negative lagged effects on economic growth. Such negative lagged effects differ among the three regions we investigated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 18 publications
0
15
1
Order By: Relevance
“…However, a comprehensive investigation of the impact of land supply on real estate investment in all prefecture-level cities has not been conducted. It is also worth noting that many studies focus on a small sample of cities or provincial-level data in studying China's real estate market (e.g., references [48][49][50][51][52][53]). Although these studies shed crucial light on the comprehension of the real estate market in China, they may offer an inadequate picture of China's real estate market given the varying socioeconomic conditions of Chinese cities.…”
Section: State Intervention In Land Supply and Its Impact On Real Estmentioning
confidence: 99%
“…However, a comprehensive investigation of the impact of land supply on real estate investment in all prefecture-level cities has not been conducted. It is also worth noting that many studies focus on a small sample of cities or provincial-level data in studying China's real estate market (e.g., references [48][49][50][51][52][53]). Although these studies shed crucial light on the comprehension of the real estate market in China, they may offer an inadequate picture of China's real estate market given the varying socioeconomic conditions of Chinese cities.…”
Section: State Intervention In Land Supply and Its Impact On Real Estmentioning
confidence: 99%
“…Besides, China's reform and opening-up from the coastal to the inland presents a sequential feature, and there is an obvious spatial imbalance in the resource allocation and factor endowments in various regions, which will also make the impact of housing investment in different regions on urban innovation show a differentiated pattern. For example, the study of Kong et al [20] found that negative lagged effects of housing investment on economic growth in China, which are different among the three regions-the eastern region shows the most significant negative effects, while the western region shows relatively insignificant. From this, we can infer that the crowding-out effect of housing investment on urban innovation also decreases from east to west in turn.…”
Section: Analysis Of the Impact Of Housing Investment On Urban Innovamentioning
confidence: 99%
“…The historical data suggests that there is bi-directional causality between economic growth and residential construction. Kong et al (2016) studied how real estate investment affects Chinese economic growth. They found that real estate investment has significantly positive contemporaneous effects on economic growth on both national and regional levels by using a dynamic panel data approach to analyze country-level and province-level data in China from 2000 to 2012.…”
Section: Introductionmentioning
confidence: 99%